The francophone African novel: historical perspective (2010)
A majority of African critics argue that literature long existed in Africa in the form of oral tradition. Novel-writing in Africa, however, can be traced back to the historical situations created by colonization. Suffice it to say that novel-writing in Africa manifested itself in different stages: a.) The French colonial novel; b.) The Emergence of the French African novel; c.) The emergence of writing by women. Each of these stages was marked by narratives and counter-narratives to debunk the misdeeds of colonizers; attack the new African leaders or correct the erroneous image given to African woman by her male counterpart in his early writings. Leaning on John Beverly’s theory on Subalternity and Representation, one notes how at various historical/literary stages, the rapport de force between the colonizer and the colonized on one hand, and the African man/woman on the other hand, was played out. The paper concludes that novel-writing in Africa since its inception has played a utilitarian function.